ANALYSIS OF THE ABILITY OF LECTURERS IN THE USE OF ONLINE LEARNING MEDIA IN THE FACULTY OF TARBIYAH AND KEGURUAN (FTK) UIN AR-RANIRY BANDA ACEH - Fathiah Fathiah; Nelli Raharti; Muhammad Rizal Fachri (Multica Science and Technology, 2021)
This study aims to describe lecturers' ability to use online learning media at the Tarbiyah and Keguruan Faculty of UIN Ar-Raniry Banda Aceh in the learning process. This study used a quantitative descriptive research design. Research subjects are lecturers who actively teach in the odd semester of 2020/2021. Meanwhile, 42 people were randomly selected as samples. Data collection was carried out using questionnaires and interviews. Data analysis used descriptive statistical analysis. The results showed that lecturers' ability with indicators of skills in using online learning media obtained an average value of 79.29%, which means that, on average, the lecturers were able to use online learning media well. The ability of lecturers with indicators of skills in managing online learning is obtained an average value of 67.56%, which means that the lecturer can manage online learning well.